2015
DOI: 10.1007/s13399-015-0166-6
|View full text |Cite
|
Sign up to set email alerts
|

Co-firing carbon dioxide-torrefied woody biomass with coal on emission characteristics

Abstract: Torrefaction is a pre-treatment technique that involves the partial pyrolysis (200-300°C) of biomass in an inert environment to improve its fuel properties. Effect of co-firing CO 2 -torrefied mesquite and juniper (10 % on mass basis) with coal in a 30-kWt downfired burner was studied considering the grindability potential of CO 2 -torrefied biomass (60 % higher grindability than N 2 -torrefied biomass). It was observed that co-firing 10 % by mass of raw mesquite with coal reduced the NO x emission from 420 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The volatiles released during biomass pyrolysis contain amounts of reducing gases, which are conducive to NO reduction. A higher CO concentration produced during co‐combustion also contributes to NO reduction . At a higher CO concentration, the reduction of NO over char is accelerated via the char/NO/CO heterogeneous reactions: CO+normalC()OCO2+Cf, 2NO+2Cf2CO+N2, 2NO+2COcharCO2+N2, where C(O) denotes a chemisorbed surface oxygen and C f denotes an active carbon site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The volatiles released during biomass pyrolysis contain amounts of reducing gases, which are conducive to NO reduction. A higher CO concentration produced during co‐combustion also contributes to NO reduction . At a higher CO concentration, the reduction of NO over char is accelerated via the char/NO/CO heterogeneous reactions: CO+normalC()OCO2+Cf, 2NO+2Cf2CO+N2, 2NO+2COcharCO2+N2, where C(O) denotes a chemisorbed surface oxygen and C f denotes an active carbon site.…”
Section: Resultsmentioning
confidence: 99%
“…Co‐combustion offers lower NOx emission, and NOx emission decreases with increasing biomass blending ratio . High CO emission during co‐combustion contributes to the decrease of NOx emission . Moreover, there is an interactive effect of co‐combustion on NOx emission in air and O 2 /CO 2 combustion .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many nations are intensively dedicated to studies of renewable energy resources to alleviate the dependence on fossil fuels [3][4][5]. Lignocellulose biomass is a significant resource for the production of fuels due to various advantages of lignocellulose biomass, including zero carbon emission, extensive availability, improved stability, and safety [6][7][8]. However, raw lignocellulose biomass has the drawbacks of high moisture content, high oxygen content, and complex variations in chemical composition [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Behera et al [1] observed that high ash coal has inferior burning profile and GCV compare to low VM coal. To reduce the impact of ash layer formed during combustion, improving VM and gross calorific value (GCV), scientists recommended blending high ash coal with high VM coal, biomass or similar feedstock [6][7][8]. Sung et al [9] and Singh et al [10] reported that biomass has better ignition and combustion properties than coal due to the presence of higher VM and highly reactive hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%